Designing Ergonomic Standing Chair for Computer Numerical Control Machine Operators using TRIZ - Rizalulhaq Rasyid; Dino Caesaron; Yusuf Nugroho Doyo Yekti (International Journal of Innovation in Enterprise System, 2023)
In this research, the working hours and posture of CNC (Computer Numerical Control) machine operators were investigated to determine the physical workload that they experienced during their daily work. Based on our observations, the operator works 8-hour regular shifts or 12-hour long shifts for 5 – 6 days a week. During these shifts, the operators work in front of the CNC machine while standing upright without any tools to rest. Preliminary research was conducted to evaluate these conditions the results show 13 out of 20 CNC machine operators complained about physical fatigue while working the CNC machines. It can also be concluded that the operators are experiencing excessive workload based on a workload assessment using the Quick Exposure Check (QEC) method. To solve this problem, a standing chair is designed with ergonomics in mind. The dimensions of the standing chair are based on the anthropometry of the CNC machine operators, which was never used before. The design process is conducted using the Theory of Inventive Problem Solving (TRIZ) methodology. Need statements from the CNC machine operators and design requirements from the stakeholders are converted into design specifications using TRIZ methodology. Parameters are determined to increase the capability of the existing design based on the design specifications. The result of this research is a standing chair that is suitable for the operator’s needs. Based on the analysis of the design result and the stress analysis simulation, it can be concluded a functional standing chair can be ergonomically designed with the TRIZ methodology.